THE ROLE OF ARTIFICIAL INTELLIGENCE IN THE ENGLISH LANGUAGE TEACHING PROCESS - Shokhista Khidiraliyeva (TADQIQOTLAR, 2026)
Annotation: The paper gives information about the growing influence of Artificial Intelligence (AI) in the field of the English language teaching process and analyzes the pedagogical role of AI in improving instructional effectiveness through individualized learning, language skill enhancement, automated assessment, and professional support for teachers.